Integrasi Kebijakan Daerah dan Tata Kelola Kolaboratif dalam Percepatan Penurunan Stunting: Studi Kasus Kota Bekasi - Episcia Puspita Lautt; Amy Yayuk Sri Rahayu (Jurnal Bina Praja, 2024)
This study analyzes the success of collaborative governance implementation in handling stunting in Bekasi City, where the stunting rate has decreased significantly from 18.18% (2018) to 2.33% (2023), far exceeding the national target of 14% for 2024. By using a qualitative case study approach, this study examines how multi-stakeholder collaboration contributed to this success. Based on the Dodeca-Helix model involving 12 stakeholder dimensions, the study revealed that effective collaborative governance is achieved through strong facilitative leadership, inclusive institutional design, and high stakeholder commitment. The collaborative framework integrates government at all levels, private sector entities, academics, and community organizations in a structured approach to stunting reduction. Data collected through in-depth interviews with key stakeholders, field observations, and document analysis show that integrating local policies with the national framework, complemented by bottom-up community participation, creates a sustainable system for stunting interventions. The experience of Bekasi City offers valuable insights for other regions developing stunting reduction programs, emphasizing the importance of multi-level policy integration, cross-sector coordination, and active community involvement. This study contributes to the theoretical understanding of collaborative governance in public health interventions and practical applications for implementing successful stunting reduction programs at the local government level.